2020
DOI: 10.3847/2041-8213/ab9eb9
|View full text |Cite
|
Sign up to set email alerts
|

NGTS-11 b (TOI-1847 b): A Transiting Warm Saturn Recovered from a TESS Single-transit Event

Abstract: We report the discovery of NGTS-11 b (=TOI-1847b), a transiting Saturn in a 35.46 day orbit around a mid K-type star (  = 5050 ± 80 K). We initially identified the system from a single-transit event in a TESS full-frame image light curve. Following 79 nights of photometric monitoring with an NGTS telescope, we observed a second full transit of NGTS-11 b approximately one year after the TESS single-transit event. The NGTS transit confirmed the par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Finally, the evolving nature of the narrative describing the KIC5951458 system is one that will become more common owing to the ongoing transit hunting efforts of TESS (Ricker et al 2015). TESS is predicted to discover on the order of 1000 single-transit events in its primary mission alone (Villanueva et al 2019;Dalba et al 2020;Eisner et al 2020;Gill et al 2020). The need to conduct imaging, photometric, and spectroscopic follow-up for many of these discoveries will place an immense burden on the pool of observational resources available to the exoplanet community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the evolving nature of the narrative describing the KIC5951458 system is one that will become more common owing to the ongoing transit hunting efforts of TESS (Ricker et al 2015). TESS is predicted to discover on the order of 1000 single-transit events in its primary mission alone (Villanueva et al 2019;Dalba et al 2020;Eisner et al 2020;Gill et al 2020). The need to conduct imaging, photometric, and spectroscopic follow-up for many of these discoveries will place an immense burden on the pool of observational resources available to the exoplanet community.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the faintness of typical Kepler host stars severely limits the list of facilities capable of making precise RV measurements. In the case of TESS single-transit detections, time baselines are shorter and host stars are brighter (e.g., Dalba et al 2020;Eisner et al 2020;Gill et al 2020), and the number of detections is expected to be much higher than for Kepler (e.g., Villanueva et al 2019). As a result, follow-up resources must be used strategically to maximize the science return from single-transit detections.…”
Section: Introductionmentioning
confidence: 99%
“…Gandolfi et al 2018;Huang et al 2018;Vanderspek et al 2019;Gilbert et al 2020) as well as discoveries of systems for which we observe only a single transit (e.g. Gill et al 2019Gill et al , 2020bLendl et al 2020), including the first monotransiting planet from TESS (Gill et al 2020a). The detection of monotransits is a natural consequence of the limited temporal coverage of TESS when compared to other surveys such as the Wide Angle Search for Planets (WASP; Pollacco et al 2006) or Kepler/K2 (Borucki et al 2010;Howell et al 2014).…”
Section: Introductionmentioning
confidence: 58%
“…These monotransits have been explored via simulations (Cooke et al 2018;Villanueva, Dragomir & Gaudi 2019), which show we can expect a large number of monotransit candidates in the TESS primary mission data. These predictions have been verified by recent monotransit searches including Montalto et al (2020) who find 15 Southern hemisphere candidates and the NGTS monotransit team (see Gill et al 2020aGill et al , 2020b for a description of the pipeline used) who have identified over 50 candidates from the first few TESS sectors alone. Many of these candidates exhibit additional extended mission transit events as discussed later in this paper.…”
Section: Introductionmentioning
confidence: 65%
“…Space-based missions such as Kepler (Borucki et al 2010), Kepler-K2 (Howell et al 2014), and CoRoT (Auvergne et al 2009) allowed the discovery and orbital characterization of the first two dozen of such systems (Bonomo et al 2010;Deeg et al 2010;Shporer et al 2017;Almenara et al 2018;Brahm et al 2018;Jordán et al 2019), but due to its significantly larger field of view, the Transiting Exoplanet Survey Satellite (TESS) mission (Ricker et al 2015) is expected to significantly increase that number (Sullivan et al 2015; Barclay et al 2018). In just its first two years of operation, TESS has demonstrated its ability to discover transiting warm Jupiters suitable for characterization follow-up (Huber et al 2019;Nielsen et al 2019;Rodriguez et al 2019;Addison et al 2020;Gill et al 2020), and this number will grow with the extended mission (Cooke et al 2019).…”
Section: Introductionmentioning
confidence: 99%